Long spelling periods are required for pasture to become free of contamination by infective larvae of Haemonchus contortus in a humid subtropical climate of São Paulo state, Brazil - Almeida, Fabiana A. [UNESP]; Albuquerque, Ana Cláudia A. [UNESP]; Bassetto, César C. [UNESP]; Starling, Renan Z.C. [UNESP]; Lins, José Gabriel G. [UNESP]; Amarante, Alessandro F.T. [UNESP] (Elsevier, 2020)
The objective of this trial was to evaluate the period of spelling necessary for a pasture to become free of contamination by infective larvae of gastrointestinal nematodes (GIN) of sheep, in different seasons of the year, as well as to determine when the greatest pasture contamination occurs and how long it lasts. An area was divided into four paddocks, one for each season (spring, summer, autumn, and winter). In order to contaminate the paddocks with free living stages of GIN, eight ewes, naturally infected, grazed on each paddock for 14 consecutive days, starting on the following dates: autumn, on April 4, 2017; winter, on July 4, 2017; spring, on September 26, 2017; summer, on January 2, 2019. At the beginning and end of the grazing period, faecal samples were taken directly from the rectums of the ewes to count eggs per gram of faeces (EPG) and for faecal cultures. Every 14 days pasture samples were collected to assess the number of infective larvae (L3) per kilogram of dry matter. At the end of the 14 day ewe grazing period, 21 stakes were placed where there were faeces on the paddock. Subsequently, every 14 days, the faeces located at three of the stakes were collected and the L3 were recovered. After the exit of the ewes, monthly, two tracer lambs, free of helminth infection, were allocated into the paddock for 14 days. At the end of this period they were housed in covered stalls for 28 days. Faeces from the lambs were collected for individual EPG counting and faecal culture at 21 and 28 days after grazing. Infective larvae recuperation was observed from faeces and pasture in all seasons. In the autumn, spring, and summer, high EPG counts were observed in the first tracer lambs (8521, 4800, and 8064 EPG, respectively), while in winter, high infection (14132 EPG) of the animals was observed only from the second pair of tracer lambs. For a pasture to become “clean”, 322 days, 350 days, 294 days, and 182 days following contamination were necessary, respectively, in the autumn, winter, spring, and summer. In autumn, spring, and summer, massive contamination of the pasture with L3 occurred soon after an area had been grazed by infected sheep, while in winter this took a little longer. The contamination persisted, approximately, from a minimum of six months post contamination in summer to up to almost one year post contamination in winter.
Keywords: Environment; Gastrointestinal nematodes; Pasture decontamination; Sheep